Clinical utility of miR-143/miR-182 levels in prognosis and risk stratification specificity of BFM-treated childhood acute lymphoblastic leukemia - Piatopoulou, D.; Avgeris, M.; Drakaki, I.; Marmarinos, A.; Xagorari, M.; Baka, M.; Pourtsidis, A.; Kossiva, L.; Gourgiotis, D.; Scorilas, A. (Ann Hematol, 2018)
Although childhood acute lymphoblastic leukemia (ALL) is characterized by high remission rates, there are still patients who experience poor response to therapy or toxic effects due to intensive treatment. In the present study, we examined the expression profile of miR-143 and miR-182 in childhood ALL and evaluated their clinical significance for patients receiving Berlin-Frankfurt-Munster (BFM) protocol. Bone marrow specimens from 125 childhood ALL patients upon diagnosis and the end-of-induction (EoI; day 33), as well as from 64 healthy control children undergone RNA extraction, polyadenylation, and reverse transcription. Expression levels of miRNAs were quantified by qPCR analysis. Patients' cytogenetic, immunohistotype and MRD evaluation was performed according to international guidelines. Median follow-up time was 86.0 months (95% CI 74.0-98.0), while patients' mean DFS and OS intervals were 112.0 months (95% CI 104.2-119.8) and 109.2 months (95% CI 101.2-117.3), respectively. Bone marrow levels of miR-143/miR-182 were significantly decreased in childhood ALL patients at diagnosis and increased in more than 90% of patients at the EoI. Patients' survival analysis highlighted that children overexpressing miR-143/miR-182 at the EoI presented significantly higher risk for short-term relapse (log-rank test: p = 0.021; Cox regression: HR = 4.911, p = 0.038) and death (log-rank test: p = 0.028; Cox regression: HR = 4.590, p = 0.046). Finally, the evaluation of the miR-143/miR-182 EoI levels along with the established disease prognostic markers resulted to improved prediction of BFM-treated patients' survival outcome and response to therapy and additionally to superior BFM risk stratification specificity. Concluding, miR-143 and miR-182 could serve as novel prognostic molecular markers for pediatric ALL treated with BFM chemotherapy.
Keywords: Adolescent; All; All ic-bfm; Antineoplastic Combined Chemotherapy Protocols/administration &; Asparaginase/administration & dosage; Berlin-Frankfurt-Munster protocol; Bone Marrow Cells/chemistry; Child; Child, Preschool; Childhood ALL; Daunorubicin/administration & dosage; Disease-Free Survival; dosage/*therapeutic use; Female; Follow-Up Studies; gene expression profiling; Greece/epidemiology; Humans; Infant; Male; MicroRNAs/*analysis; miRNA; Neoplasm, Residual; Non-coding RNA; Precursor Cell Lymphoblastic Leukemia-Lymphoma/drug; Prednisone/administration & dosage; Prognosis; Proportional Hazards Models; Real-Time Polymerase Chain Reaction; Remission Induction; Risk Assessment; RNA, Neoplasm/*analysis; therapy/*genetics/mortality/pathology; Treatment Outcome; Vincristine/administration & dosage